Performance, nutrient use, and methanogenesis of Nellore cattle on a continuous grazing system of Urochloa brizantha and fed supplement types varying on protein and energy sources - Ferrari, Adriana C. [UNESP]; Leite, Rhaony G. [UNESP]; Fonseca, Natália V.B. [UNESP]; Romanzini, Eliéder P. [UNESP]; Cardoso, Abmael da S. [UNESP]; Barbero, Rondineli P.; Costa, Diogo F.A.; Ruggieri, Ana C. [UNESP]; Reis, Ricardo A. [UNESP] (Elsevier, 2021)
Supplementation of grazing cattle may improve forage utilization, methane emission and efficiency of nutrients use. This study aimed to evaluate the effect of different supllementation strategies on performance, metabolic parameters and methane emission in Nellore cattle reared on well-managed marandu palisadegrass (Urochloa brizantha cv Marandu) pastures. Three supplementation strategies consisted of protein and energy sources from traditional ingredients compared to a novel feedstuff: TS) Traditional supplement (protein-energy) composed of ground corn and soybean meal; ES) energy supplement composed of ground corn; and DS) Distiller's coproduct supplement (protein-energy) composed of ground corn and dried distiller grain (DDG). All supplements were offered at 0.3% of body weight (BW). Sixty-nine growing Nellore bulls [251 kg of body weight (BW) ± 13.0 kg] were randomly distributed according to initial BW in nine paddocks (twenty-three animals per treatment, three paddocks per treatment) to evaluate liveweight gain. From these, eighteen bulls (381.83 kg BW ± 16.15 kg) were selected for methane emission measurements (six animals per treatment) using sulfur hexafluoride tracer gas technique. Six rumen cannulated steers (289.5 kg BW ± 19.6 kg) across six paddocks (two per treatment) were used in an incomplete double Latin square design (3 treatments x 4 periods) to evaluate metabolic parameters. Statistical analyses were done using the Mixed Procedure in SAS and adopting significance level at 5%. It was hypothesized that the use of DS or ES, could increase the N use efficiency because of a higher rumen undegradable protein content, and more energy available for microbial synthesis in the rumen, respectively. Overall, there were no differences on animal performance, intake, nutrients digestibility, ruminal parameters, and microbial protein synthesis among treatments indicating that any of the supplemental sources could be utilized. Although, animals in DS had lower urine N excretion. The ES supplement increased methane yield (g/DMI) and the methane conversion factor Ym (% of gross energy intake) when compared to other treatments, but not methane production, which was similar among all treatments.
Keywords: Greenhouse gas; Novel source; Strategic supplementation; Tropical grass